Productive Capacities and the SDGs: Critical but Nuanced Relationships - David Tennant; Stuart Davies; Sandria N. Tennant; Patrice Whitely (Managing Global Transitions)
It is widely accepted that productive capacities are an enabler for the UN sustainable development goals (SDGs), but there is a dearth of literature empirically testing this view. This paper examines the relationships between productive capacities and the SDGs and reveals nuances that need to be accounted for in integrated development approaches. Using panel data time series models, with Driscoll-Kraay adjusted standard errors, we examine how enhancing the eight elements of the Productive Capacity Index (PCI) impacts the SDGs. We find that each of the SDGs has statistically significant relationships with multiple elements of the PCI, and the results highlight areas in which productive capacity enhancements accelerate progress on one or more SDGs but can also be inimical to others, particularly to goals related to the environment and income inequality. Our approach provides development practitioners with a new framework to better target SDG interventions.